2018
DOI: 10.1111/1750-3841.14125
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of an β‐N‐Acetylhexosaminidase from Bacillus sp. CH11, Including its Transglycosylation Activity

Abstract: The new transfer products including 1-O-β-D-N-acetylglucosaminyl xylitol are attractive compounds for their potential physiological functions. 1-O-β-D-N-Acetylglucosaminyl xylitol was produced effectively from chitin-oligosaccharides and xylitol by β-N-acetylhexosaminidase from Bacillus sp. CH11. This enzyme may be useful for the development of food materials for health-related applications such as oligosaccharides with intestinal functions and noncariogenic sugars.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…A change in optimal pH was also reported for the transglycosylation catalyzed by β‐ N ‐acetylhexosaminidase Bacillus sp. CH11 (Kurakake et al., 2018).…”
Section: Results and Disccusionmentioning
confidence: 99%
See 2 more Smart Citations
“…A change in optimal pH was also reported for the transglycosylation catalyzed by β‐ N ‐acetylhexosaminidase Bacillus sp. CH11 (Kurakake et al., 2018).…”
Section: Results and Disccusionmentioning
confidence: 99%
“…After centrifugation through a 0.22‐µm membrane filter at 10,000 × g for 5 min, the filtrate was analyzed by high‐performance liquid chromatography (HPLC). The transfer ratio [ G 3/( G 3 + ( G 1 – G 3)/2) × 100(%)] was calculated from the concentrations (M) of N ‐acetylglucosamine ( G 1) and N , N′ , N″ ‐triacetylchitotriose ( G 3) in the transfer product (Kurakake et al., 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings demonstrated that the two endo-1,3-β-glucanases from mollusks exhibit different transglycosylation specificities, although they share a high sequence identity. The unique transglycosylation activity of L cf towards sorbitol facilitates the development of glycoconjugates with intestinal functions, and noncariogenic sugars [ 35 ]. In sum, this study provided insights into novel endo-1,3-β-glucanases from marine mollusks, enhancing our understanding of the diverse enzymatic specificities of marine mollusk endo-1,3-β-glucanases.…”
Section: Resultsmentioning
confidence: 99%
“…H11 25 , the β-glucosidases CelB from Pyrococcus furiosus 26 and SSG from Sulfolobus shibatae 27 , the β-galactosidases Bgal from Kluyveromyces lactis 28 and LacA from Aspergillus oryzae 29 , or the β-N-acetylhexosaminidase from Bacillus sp. CH11 30 . However, to the best of our knowledge, there are no known β-fructofuranosidases described to generate such compounds other than that from Arthrobacter sp.…”
Section: Introductionmentioning
confidence: 99%